Default supply auctions in electricity markets: Challenges and proposals. (November 2018) - Peña, Juan Ignacio; Rodriguez, Rosa
Abstract: This paper studies premiums got by winning bidders in default supply auctions, and speculation and hedging activities in power derivatives markets in dates near auctions. Data includes fifty-six auction prices from 2007 to 2013, those of CESUR in the Spanish OMEL electricity market, and those of Basic Generation Service auctions (PJM-BGS) in New Jersey's PJM market. Winning bidders got an average ex-post yearly forward premium of 7% (CESUR) and 38% (PJM-BGS). The premium using an index of futures prices is 1.08% (CESUR) and 24% (PJM-BGS). Ex-post forward premium is negatively related to the number of bidders and spot price volatility. In CESUR, hedging-driven trading in power derivatives markets predominates around auction dates, but in PJM-BGS, speculation-driven trading prevails. The policy recommendation to market regulators and administrators is that they should gauge consumers' price risk aversion before introducing alternative methods to default supply auctions for the computation of the part of cost of energy of the electricity bill of customers whose contracted capacity is small and are not served by other suppliers. Highlights: Ex-post forward yearly premium in 2007–2013 is 7% (CESUR) and 38% (PJM-BGS). The premium using an index of futures prices is 1.08% (CESUR) and 24% (PJM-BGS). Premium is negatively related to number of bidders and spot price volatility. Power derivatives trading is for hedging (speculation) in CESUR (PJM-BGS). Gauge consumers' price risk aversion before introducing alternative methods to DSA.